Synthesis and Characterization of Alkaline Earth Metal Chelates of Phthiocolmonoxime - Kanase, D.G.; Kadam, S.S.; Takale, S.T.; Kelkar, V.D. (Asian Journal of Chemistry, 2010)
Metal chelates of phthiocolmonoxime with beryllium(II), magnesium(II), calcium(II), strontium(II) and barium(II) were synthesized and there chemical identities were established on the basis of elemental analysis. The structural investigations were carried out using infrared spectra and electronic spectra. The molecular composition of all the chelates corresponds to [ML2.(H2O)2] except for beryllium(II) chelate in which it is [ML(OH)]2.2H2O. A dimeric structure for tetrahedrally surrounded metal ion with bridging hydroxo group is proposed for beryllium(II) chelates, while trans-octahedral structure is suggested for all other chelates.